Understanding Brewing Trait Inheritance in de Novo Lager Yeast Hybrids - Cubillos-Riffo, F; Saona-Acuna, L (American Society for Microbiology, 2024)
Hybridization between Saccharomyces cerevisiae and Saccharomyces eubayanus resulted in the emergence of S. pastorianus, a crucial yeast for lager fermentation. However, our understanding of hybridization success and hybrid vigor between these two species remains limited due to the scarcity of S. eubayanus parental strains. Here, we explore hybridization success and the impact of hybridization on fermentation performance and volatile compound profiles in newly formed lager hybrids. By selecting parental candidates spanning a diverse array of lineages from both species, we reveal that the Beer and PB-2 lineages exhibit high rates of hybridization success in S. cerevisiae and S. eubayanus, respectively. Polyploid hybrids were generated through a spontaneous diploid hybridization technique (rare-mating), revealing a prevalence of triploids and diploids over tetraploids. Despite the absence of heterosis in fermentative capacity, hybrids displayed phenotypic variability, notably influenced by maltotriose consumption. Interestingly, ploidy levels did not significantly correlate with fermentative capacity, although triploids exhibited greater phenotypic variability. The S. cerevisiae parental lineages primarily influenced volatile compound profiles, with significant differences in aroma production. Interestingly, hybrids emerging from the Beer S. cerevisiae parental lineages exhibited a volatile compound profile resembling the corresponding S. eubayanus parent. This pattern may result from the dominant inheritance of the S. eubayanus aroma profile, as suggested by the over-expression of genes related to alcohol metabolism and acetate synthesis in hybrids including the Beer S. cerevisiae lineage. Our findings suggest complex interactions between parental lineages and hybridization outcomes, highlighting the potential for creating yeasts with distinct brewing traits through hybridization strategies. © © 2024 Zavaleta et al.